Antimicrobial activity of the three commercial drug’s essential oils: Chamomillae flos, Calendulae flos and Millefolii herba - Stojanović-Radić, Z (Biologica Nyssana, 2012)
Commercial herbal drugs of the three plants belonging to family Asteraceae were used for the extraction of the essential oils (hydrodistillation method). Since various factors during the processing of the plant material can affect several characteristics of essential oils such as yield, chemical composition and, thus, biological activities of essential oils, comparison of the antimicrobial activity of the herein isolated oils was done with avaiable literature sources dealing with this subject. In order to evaluate antimicrobial potential of the isolated essential oils, a broth microdilution method was employed. The results pointed to very high activity of the tested oils, in all cases much stronger in comparison to the previous results. As a conclusion, the adverse effects of plant material processing did not affect its antimicrobial potential, while the obtained high antimicrobial activity can be explained by sinergistic action of the herein used solvent with essential oils.